LOGARITHMS
CONTENT
- Revision of the Laws of Indices
- Indices Involving Powers in Simultaneous Lnear Equations
- Laws of Logarithms
- Logarithmic Equations
Revision of the Laws of Indices
The expression \(a^n\) means \(a\) is multiplied by itself \(n\) times, e.g.
\(2^4 = 2 × 2 × 2 × 2 = 16\), \(3^5 = 3 × 3 × 3 × 3 ×3 = 243\)
(i) \(a^m × a^n = a^{m+n}\) Example: \(2^5 × 2^2 = 2^{5+2} = 2^7\)
(ii) \(\frac{a^m}{a^n}\) or
\(a^m÷a^n=a^{m-n}\) Example: \(\frac{3^5}{3^3}=3^{5 -3} = 3^2\)
(iii) \((a^m)^n=a^{mn} \) Example: \((2^2)^3=2^{2×3}=2^6 \)
(iv) \(\frac{1}{a^n} =a^{-n}\) Example: \(\frac{1}{3^2} =3^{-2}\)
(v) \(a^o = 1\) Example: \(5^o = 1\)
(vi) \(a^{\frac{1}{n}} = \sqrt[n]{a}\) Example: \(8^{\frac{1}{3}} = \sqrt[3]{8} = 2\)
(vii) If \(a^x = a^y\), then \(x = y\) Example: If \(2^m = 2^n\), then \(m = n\)
Examples:
1. Evaluate \(9^{\frac{-1}{2}}\)
Solution:
\(9^{\frac{-1}{2}}=(3^2 )^{\frac{-1}{2}}=3^{2 ×\frac{-1}{2}}=3^{-1}= \frac{1}{3}\)
2. Evaluate \(81^{\frac{1}{4}}\)
Solution:
\(81^{\frac{1}{4}} = (3^4)^{\frac{1}{4}} = 3^1 = 3\)
3. Evaluate \(\Big(\frac{1}{4}\Big)^{\frac{-1}{2}}\)
Solution:
\(\Big(\frac{1}{4}\Big)^{\frac{-1}{2}} = \Big(\frac{1}{2^2}\Big)^{\frac{-1}{2}} = (2^{-2})^{\frac{-1}{2}} = 2^{-2 × \frac{-1}{2}} = 2\)
4. Simplify \(\frac{16}{8^{\frac{-2}{3}}}\)
Solution:
\(\frac{16}{8^{\frac{-2}{3}}} = 16 ÷ 8^{\frac{-2}{3}} = 16 ÷ \frac{1}{8^{\frac{2}{3}}} \\ = 16 × 8^{\frac{2}{3}} = 2^4 × 2^{\Big(3×\frac{2}{3}\Big)} = 2^4 × 2^2 = 2^6 = 64\)
5. \(\frac{27^{\frac{2}{3}} × 81^{\frac{1}{4}}}{9^{\frac{3}{2}}}\)
Solution:
\(\frac{27^{\frac{2}{3}} × 81^{\frac{1}{4}}}{9^{\frac{3}{2}}} = \frac{(3^3)^{\frac{2}{3}} × (3^4)^{\frac{1}{4}}}{(3^2)^{\frac{3}{2}}} \\ = \frac{3^2 × 3^1}{3^3} \\ = \frac{3^3}{3^3} = 1\)
6. Simplify \((2a^2 b)^2 (-a^2 b)^3\)
Solution:
\((2a^2 b)^2 (-a^2 b)^3 = (4a^4b^2)(-a^6b^3) \\ = -4a^{4+6}b^{2+3} \\ = -4a^{10}b^5\)
7. Simplify \((2xy)^2 + (-y)(4xy)(-2x)\)
Solution:
\((2xy)^2+(-y)(4xy)(-2x) = 4x^2 y^2+(-y)(-8x^2y) \\ = 4x^2 y^2+8x^2 y^2 \\ = 12x^2 y^2\)
CLASS ACTIVITY
Simplify the following:
1. \(\sqrt[3]{\Big(\frac{8}{27}\Big)^2}\)
2. \(\sqrt[4]{\Big(5\frac{1}{16}\Big)^{-3}}\)
3. \(\frac{15a^3 b^5}{5ab^2}\)
Further Examples
Solve for \(x\):
\(3^{2x+1} = 243\) (WAEC SSCE)
Solution:
\(3^{2x+1} = 243\)
Express the R.H.S in power to base 3
\(3^{2x+1} = 3^5\)
Equating the powers, we have
\(2x + 1 = 5 \\ 2x = 5 -1 \\ 2x = 4 \\ x = 2\)
2. Solve for \(x\): \(2^{x + 2} = 8^{x -2}\) (WAEC SSCE)
Solution:
Express the R.H.S in power to base 2
\(2^{x + 2} = 2^{3(x -2)} \\ 2^{x + 2} = 2^{3x -6}\)
Equating the powers, we have
\(x + 2 = 3x -6 \\ x -3x = -6 -2 \\ -2x = -8 \\ x = 4\)
3. \(x^4 = (0.25)^2\); find \(x\).
Solution:
\(x^4 = (0.25)^2 \\ x^4 = \Big(\frac{25}{100}\Big)^2\)
We will seek to make R.H.S in powers of 4
\( x^4 = \Big(\frac{5^2}{10^2}\Big)^2 \\ x^4 = \Big(\frac{5}{10}\Big)^4 \)
Equating terms having equal powers, we have
\( x = \frac{5}{10} \\ x = 0.5\)
CLASS ACTIVITY
1. If \(4^x = 2^{\frac{1}{2}} × 8\), find \(x\)
2. If \(8^{\frac{x}{2}} = 2^{\frac{3}{8}} × 4^{\frac{3}{4}}\), find \(x\)
3. Given that \(125^{2x+1} = 625 × 25^{-x}\), find \(x\)
4. If \(3^m × 27^{(2m -1)} = 81\), find \(m\)
Indices Involving Powers in Simultaneous Lnear Equations
Example1: If \(3^{y+x} = 9^{y+x}\) and \(2^{x-y} = 8^{x -3}\), find the values of \(x\) and \(y\) respectively.
Solution:
If \(3^{y+x}=9^{y+x} \) and \(2^{x -y}=8^{x -3}\), then expressing both equations in the powers of their common base, we have
\(3{y+x}=3^{2(y+x)} ⇒ 3^{y+x}=3^{2y+2x}\) ………(i)
\(2^{x -y}=2^{3(x -3)} ⇒ 2^{x -y}=2^{3x -9}\) ……….(ii)
Equating the powers of equations (i) & (ii)
\(y+x=2y+2x ⇒x+y=0\) ………….(iii)
\(x -y=3x-9 ⇒2x+y=9\) …………(iv)
Solving equations (iii) & (iv) simultaneously, We obtain \(x = 9 , y= -9\)
Examples:
Solve the equation \(4^{x+1} -9(2^x) = -2\) (WAEC SSCE)
Solution:
\(4^{x+1} -9(2^x) = -2 \\ 4^{x+1} -9 (2^x)+2=0 \\ 4(4^x ) -9 (2^x)+2=0 \\4(2^2x) -9(2^x)+2=0 \\ 4(2^x )^2 -9(2^x)+2=0\)
Since \(2^{3×2} =(2^3 )^2 \)
let \(p=2^x\), then the equation becomes
\(4p^2 -9p+2=0\)
Factorizing we have;
\(4p^2 -8p -p+2=0 \\ 4p(p -2) -1(p -2)=0 \\ (p -2)(4p -1)=0 \\ ⇒p -2=0 \text{ or } 4p -1=0 p=2 \text{ or } p=\frac{1}{4}\)
Remember that \(p=2^x\) When \(p=2\), note that \(2\) is the same as \(2^1\).
\(2^x=2^1 \\ ∴ x = 1\)
When \(p= \frac{1}{4} \\ 2^x=\frac{1}{4} 2^x=2^{-2} ∴ x= -2\)
So, the solution of the equation is \(x=1\) and \(x= -2\)
CLASS ACTIVITY
- Find the value of \(x\) given that \(7×49^{(x+2)} = \frac{1}{343} \)
- Solve simultaneously for x and y; \(4^x×8^y=256\) and \(8^x×\frac{1}{4^y} =\frac{1}{2}\)
- Find the values of \(x\) & \(y\), given that \(3^x × \frac{1}{3^y} = 9^3\) and \(9^x×3^y=27\)
- Find the values of \(x\) & \(y\), given that \(5^x × \frac{1}{5^y} =5\) and \(5^x×5^y=125\)
- Given that \(\frac{1}{3}\) of \(27^x=9^{2x}\), find \(x\)
- For what values of \(x\) is \(125^{\frac{-2}{x}}=\frac{1}{25} \)?
- Simplify \(125^{\frac{-1}{3}}×49^{\frac{-1}{2}}×10^0\)
- Simplify \(\frac{27^{\frac{2}{3}} × 64^{\frac{-1}{2}}}{32^{\frac{-2}{5}}}\)
- Simplify the following: (i) \(27^{\frac{1}{3}}\) (ii) \(16^{-\frac{1}{4}}\) (iii) \(125^{-\frac{1}{3}}\) (iv) \((8\frac{1}{3})^{-2}\) (v) \(y^{\frac{1}{2}} × y^{-1} × y^{\frac{3}{2}}\) (vi) Find \(x\), given that \(9×3^{1+x} = 27^{-x}\)
- Simplify the following: (a) \(25^{\frac{-3}{2}}\) (b) \(81^{\frac{3}{4}}\) (c) \(\Big(\frac{1}{4}\Big)^{\frac{-3}{2}}\) (d) \((x^3)^{\frac{-2}{3}}\) (e) \((z^0)^{\frac{1}{4}}\) (f) \(\frac{27^{\frac{1}{3}}}{16^{-\frac{1}{4}}}\) \(64^{\frac{1}{2}}×9^{\frac{3}{2}}×2^{-5}\)
- Without using mathematical tables, simplify leaving your answer in standard form (a) \(\sqrt{\frac{8.1 × 10^{-5}}{1.44 × 10^4}}\) (b) \(\sqrt{\frac{250 × 10^7}{1.21 × 10^4}}\)
- Simplify \(\frac{1}{3^{5n}} × 9^{n -1} × 27^{n + 1}\)
- Solve the equation for \(x\); \(3^{2x+2} -28(3^x) + 3 = 0\)
- Solve for x and y;
- \(x\); \(\frac{9^y}{81} = \frac{9}{3^x} \) and \(\frac{27^x}{3^{y -8}} = \frac{1}{9} \)
- Solve simultaneously; \(32^{x -1} × 8^y × \frac{1}{16} = 8\) and \(2^x × \frac{1}{8^y} = 64\)
Logarithms
This aspect of logarithm deals with applying the relationship between indices and logarithm and laws of logarithm to solve problems. The logarithm of any number to a given base is the index or power to which the base must be raised so that it is equal to that number. If \(N = b^x\), then \(log_bN=x\), that is, the logarithm to base \(‘b’\) of a number \(N\), is the index (power \(x\)) to which ‘\(b\)’ must be raised to be equal to \(N\). The relations \(log_bN=x\) and \(b^x=N\) are equivalent to each other. The form \(b^x=N\) is called the index form of writing numbers, while the form \(log_bN=x\) is called the logarithmic form. This implies that for every logarithmic equation, there must be a corresponding index equation.
Examples:
1. \(log_{28}=3 ⇒2^3=8 \)
2. \(log_{10} 1000=3 ⇒ 10^3=1000\)
3. \(log_381=4 ⇒ 3^4=81\)
4. \(log_2 \sqrt{8} = \frac{3}{2} ⇒ 2^{\frac{2}{3}} = \sqrt{8}\)
5. \(log_2 \frac{1}{32} = -5 ⇒ 2^{-5}= \frac{1}{32}\)
The definition of \(log_ax\) can also be stated as follows:
For any \(a > 0\) and \(a≠1\)
\(y = log_ax\) if and only if \(a^y=x\)
NB: The base of a logarithm must be a positive number and cannot be \(1\).
Examples:
Evaluate the following without using tables or calculator.
(a) \(log_40.0625 \)
(b) \(log_{0.25}128\)
(c) \(log_{\sqrt[2]{2}}\sqrt{128}\)
(d) \(log_{10}0.001\)
Solution:
(a) \(log_40.0625\)
Let \(log_40.0625=x \)
Then \(4^x=0.0625 \\ 4^x=\frac{625}{10000}=\frac{1}{16} \\ 4^x=\frac{1}{4}^2 \\ 4^x=4^{-2} \)
Equating powers
\(∴ x= -2\)
(b) \(log_{0.25}128 \)
Let \(log_{0.25}128=y \\ (0.25)^y=128 \\ \Big(\frac{1}{4}\Big)^y=128 \\\Big(\frac{1}{2^2}\Big)^y=2^7 \\ 2^{-2y}=2^7\)
Equating powers
\(-2y=7 \\ ∴ y = \frac{-7}{2}\)
(c) \(log_{\sqrt[2]{2}}\sqrt{128}\)
Let \(log_{\sqrt[2]{2}}\sqrt{128} = p \\ (\sqrt[2]{2})^p=\sqrt{128} \\ \Big(2^{\frac{3}{2}}\Big)^p =128^{\frac{1}{2}} \\ 2^{\frac{3p}{2}}=2^{\frac{7}{2}}\)
Equating powers
\(\frac{3p}{2}=\frac{7}{2} \)
Cross-multiply
\(6p=14 \\ \frac{6p}{6}=\frac{14}{6} \)
∴ \(p=\frac{7}{3}\) or \(2 \frac{1}{3}\)
Let \(log_{10}0.001 = m\)
\(10^m=0.001 \\ 10^m=\frac{1}{1000} \\ 10^m=\frac{1}{10^3} \\ 10^m=10^{-3} \\ ∴ m= -3\)
CLASS ACTIVITY
1. Express the following in index form.
(a) \(log_39=2\)
(b) \(log_3x=10\)
(c) \(log_ct=4\)
(d) \(log_50.04=-2\)
Express the following in logarithm form.
(a) \(p^3=m \)
(b) \(64=16^{\frac{3}{2}} \)
(c) \(\Big(\frac{1}{3}\Big)^{-3}=27 \)
(d) \(0.001=10^{-3} \)
(e) \(2^x=4\sqrt{2}\)
PRACTICE EXERCISES
Evaluate the following (without using tables or calculator) with the use of the relationship between indices and logarithms.
1. \(log_{12}144\)
2. \(log_41\)
3. \(log_{0.5} \Big(\frac{1}{64}\Big)\)
4. \(log_{\sqrt{2}2}\)
5. \(log_{10}\sqrt{10}\)
Laws of Logarithm
The following are the different rules that may be applied when solving problems on logarithms.
1. Addition Law
\(log_bMN=log_bM+log_bN\)
This implies that when two logarithms of the same base are multiplied, the result is the addition of the two logarithms to their common base.
Example:
\(log_{10} 72 = log_{10}(10×7.2)=log_{10}10+log_{10}7.2\)
2. Subtraction Law
\(log_b\Big(\frac{M}{N}\Big) = log_bM -log_bN\)
This shows that when logarithms are divided, the logarithm of the denominator is subtracted from the logarithm of the numerator in their common base.
Example:
\(log_{10}0.3=log_{10}\Big(\frac{3}{10}\Big)=log_{10}3 -log_{10}10\)
3. Logarithm of its Own Base
The logarithm of any number to its own base is equal to \(1\).
Example:
\(log_55=1\), \(log_{\sqrt{7}}sqrt{7}=1\), \(log_{\frac{2}{3}}\Big(\frac{2}{3}\Big)=1\), etc.
4. Power Law
\(log_bN^k= klog_bN\)
When a logarithm is raised to a certain power, the power is used to multiply the logarithm itself.
Example 1:
\(log_{10}10^3=3log_{10}10 \\ =3×1=3 \)
Note: \( log_aa=1\)
Example 2:
\(log_28^3=3 log_28 \\ =3log_22^3 \\ =3×3 log_22 \\ =3×3×1\)
\(=9\) since \(log_22=1\)
5. Power of the Base
\(log_{a^2 }x = \frac{1}{2} log_ax\)
When it is the base that has a power, the reciprocal of this power is used to multiply the logarithm itself.
Example 1:
\(log_{2^3}16=\frac{1}{3} log_216 \\ = \frac{1}{3} log_22^4 \\= \frac{4}{3} log_22 = \frac{4}{3}×1=\frac{4}{3}\)
Example 2:
\(log_{\sqrt{9}}27=log_{9^{\frac{1}{2}}}27 \\ = 2 log_9 27 \\ = 2 log_(3^2 )27 \\ = 2× \frac{1}{2} log_327 \\ = log_33^3 \\= 3 log_33=3×1=3\)
6. Logarithm of 1
\(log_b1=0 \)
The logarithm of 1 to any base is equal to zero i.e \(log_3 1=0\), \(log_10 1=0\), \(log_7 1=0 \)
Example:
If \(log_{10}1=x \)
Then, \(10^x=1 \)
But we know that any number raised to power zero is 1
So that, \(10^x=10^0\)
∴ \(x=0\)
Showing that \(log_{10} 1=0\)
7. Reciprocal Law
\(log_ax=\frac{1}{log_xa}\)
When the reciprocal of a logarithm is required, the base and the number interchange their positions.
Example:
\(log_48=\frac{1}{log_84}\)
8. Change of Base
\(log_ax=\frac{log_nx}{log_na} \)
Example:
\(log_38=\frac{log_{10}8}{log_{10}3}\), \(log_{\sqrt{2}}16=\frac{log_{10}16}{log_{10}\sqrt{2}}\), etc.
This shows that when the base of a logarithm is changed, the initial base is used as a separate logarithm to divide the initial logarithm to the new base.
General Examples
Simplify \(\frac{log\sqrt{27}}{log 9}\)
Solution:
\(\frac{log 27^{\frac{1}{2}}}{log 9} = \frac{log 3^{\frac{3}{2}}}{log 3^2} \\ = \frac{\frac{3}{2} log 3}{2 log 3} \\ = \frac{3}{2} ÷ \frac{2}{1} \\ = \frac{3}{2} × \frac{1}{2} \\ = \frac{3}{4}\)
2. Simplify \(log_{10} \sqrt{20} + log_{10}5 -log_{10}\sqrt{5}\)
Solution:
\(log_{10} 2\sqrt{5} + log_{10}5 -log_{10}\sqrt{5} = log_{10} \Big(\frac{2\sqrt{5} × 5}{\sqrt{5}}\Big) \\ = log_{10}(2 × 5) \\ = log_{10}10 \\ = 1\)
3. Evaluate \(x\) if \(log_1010^x=3x+2\)
Solution:
\(10^x=10^{3x+2}\)
Equating powers
\(x=3x+2⇒x= -1\)
Find \(x\), if \(log_4 (x+3)(x -3) =2\)
Solution:
\(log_4 (x^2 -9) = 2 \\ (x^2 -9)=4^2 \\ (x^2 -9)=16 \\x^2=16+9=25 \\ x^2=5^2\)
We have to equate the base since the powers are the same
\(⇒x=5\)
Find the value of \(x\) given that \(log_{10}5+log_{10}(x+2) -log_{10}(x -1)=2\) (WAEC SSCE)
Solution:
Using the combined laws of logarithm (addition and subtraction laws), we have
\(log_{10} \Big(\frac{5(x + 2)}{x -1}\Big) = 2 \\ \frac{5(x + 2)}{x -1} = 10^2 \\ 5(x+2)=100(x -1) \\ 5x+10=100x -100 \\5x -100x= -100 -10 \\ -95x= -110 \\ x=\frac{-110}{-95} \\ ∴ x=1 \frac{3}{19}\)
Try this yourself: Simplify \(log_{10}10 -2log_{10} \Big( \frac{1}{5}\Big) -log_{10}2.5\) (The answer is \(2\))
Substitution in Logarithm
Given that \(log3=0.4771\), \(log2=0.3010\), find the values of the following without using logarithm table. (NECO 2002 Q5)
(i) \(log\sqrt{6} \)
(ii) \(log\sqrt[3]{0.3}\)
Solution:
\(log\sqrt{6} = log6^{\frac{1}{2}} \\ = \frac{1}{2} log6 = \frac{1}{2} log (2×3)\)
Applying the addition law of logarithm, we have
= \(\frac{1}{2}(log2+log3)\) But we were given \(log2=0.3010\) and \(log 3=0.4771\)
= \(\frac{1}{2}(0.3010+0.4771) \\ =\frac{0.7781}{2} = 0.38905 \\ log sqrt[3]{0.3} = log (0.3)^{\frac{1}{3}} \\ = \frac{1}{3} log (0.3) \\ = \frac{1}{3} log\Big(\frac{3}{10}\Big) \\ = \frac{1}{3} (log3 -log{10}) \\ = \frac{1}{3} (log3 -1) = \frac{1}{3}(0.4771 -1) \\ = \frac{-0.5229}{3} \\ = -0.1743\)
If \(log2 = 0.3010\) and \(log3=0.4771\), calculate without using tables the value of \(log 0.72\)
Solution:
Log \(0.72 = log\Big(\frac{72}{100}\Big) \\ = log 72 -log100 \\ = log (8×9) -log 10^2 \\ = log 8 + log9 -log 10^2 \\ = log 2^3 + log 3^2 -log 10^2 \\ =3 log2 + 2log3 -2log10 \\ =3(0.3010) + 2(0.4771) -2(1) \\ =0.9030+0.9542 -2 \\ = -0.1428\)
8. Given that \(log_{10} 5=0.699\) and \(log_{10} 3=0.4771\), find \(log_{10}45\) without using mathematical tables, hence solve \(x^{0.8265}=45\)
Solution:
\(log_{10} 45 = log_{10} (9×5) \\ = log_{10}9+log_{10}5 \\ = log_{10} 3^2 + log_{10} 5 \\ = 2 log_{10}3+log_{10}5 \\ = 2(0.4771)+(0.699) \\ = 1.653\)
For \(x^{0.8265}=45\), we take logarithm to base ten of both sides;
i.e. \(log_{10} x^{0.8265}= log_{10}45 \\ 0.8265 log_{10}x=log_{10}45 \)
But \(log_{10} 45=1.653\) from above
\(0.8265 log_{10}x=1.653 \\ log_{10}x=\frac{1.653}{0.8265} \\ log_{10}x=2 \\ x = 10^2 \\ ∴ x=100\)
PRACTICE EXERCISES
1. Given that \(log2=0.3010\), \(log3=0.4771\) and \(log7=0.8451\), evaluate the following:
(a) \(log63\) (b) \(log84\) (c) \(log20\) (d) \(log140\)
2. Evaluate the following as logarithm of single numbers.
(a) \(2 -log25\) (b) \(2 log4 -log8\) (c) \(log3+log15 -log5\) (d) \(3 log5+log2 -log50\) (e) \(log5+log8 -1\)
ASSIGNMENT
1. Given that \(logx -log (2x -1)=1\), find \(x\) (WAEC)
2. Evaluate without any tables \(3 log2+log20 -log1.6\) (WAEC)
3. Solve the equation: \(log_2 (x^2 -2) = log_2 (x -1)+1\) (WAEC)
4. Evaluate \(log_{10} \sqrt{35}+log_{10} \sqrt{2} -log_{10} \sqrt{7}\) (WAEC)
5. Evaluate \(log_{10}50+log_{10}64 -log_{10}32\) (WAEC)
6. If \(log_{10}(2x+1) -log_10(3x -2)=1\), find \(x\)
7. If \(log_{10}(3x -1) -log_{10}2=3\), find \(x \)
8. Simplify \(\frac{log\sqrt{8}}{log8}\)
9. Without using mathematical tables, find \(x\) given that \(6 log (x+4)=log64 \)
10. If \(log_ax=p\) and \(log_a y=q\), show that \(xy=a^{p+q}\), deduce that \(log_a xy =log_a x+log_ay\)
KEYWORDS
logarithms, log, index, power, log, root, square, etc.
- NEW: Download the entire term's content in MS Word document format (1-year plan only)
- The complete lesson note and evaluation questions for this topic
- The complete lessons for the subject and class (First Term, Second Term & Third Term)
- Media-rich, interactive and gamified content
- End-of-lesson objective questions with detailed explanations to force mastery of content
- Simulated termly preparatory examination questions
- Discussion boards on all lessons and subjects
- Guaranteed learning